Contemporary formation indicators of free zones cities -Public Free zones models- - Mohammed Hassan , Rand; Hassan Jasim, Adil (Journal of Planner and Development, 2023)
The free zone or the free economy cities are cities with classification and functional specificity, although the history of  the concept of these areas has been It dates back to distant eras, but the intellectual and philosophical construction with the support of intellectual approaches, the most important of which is globalization contributed to its rapid spread globally and taking a variety of forms and models. With the diversity of its formulas and objectives countries have competed in adopting the establishment of these areas, meanwhile The influence of related trends affected the contemporary formation of these sites. Therefore ,the research was directed focus on the importance of adopting a set of common indicators (collection between different formulas) these indicators ensure the formation of spatial formulas and urban structure for the model of cities and free zones with the influence of propositions and renewed proposals and connections that have a role in the process of creating an effective and influential structure within the location dimension and operational - activation within the functional dimension of these areas. the synthetic formula deduced according to the indicators represents the new phase of the free economic zones according to the  perspective of contemporary vision. For thus , the research problem was identified by the weakness of existence of common indicators between the different forms of free zones indicated in accordance with contemporary trends to establish an urban structure that contributes solving new problems in hose areas . this is on  assumption that adopting of form of indicators contributes to providing the formation of a contemporary urban structure contributing to the construction of specialized cities models with special functional efficiency and effectiveness that developed to verification different goals , and multi changes in the best way.Therefore , the important of research is evident because it is  providing measures in form of indicators for multiple levels that enable both planners , decision makers to crystallize the foundations to create an environment closer to the model. To achieve the hypothesis .The research adopts the descriptive analysis approach to deal with the theoretical foundations , while reviewing a number of selected experiment for models of various economic regions free zones to extract  the axes of the research indicators to present , Thus , researching a common level of standards for formulas of economic regions in building models that are more efficient and flexible to changes.